LEVEL OF COORDINATION AND MOTOR SKILLS FOR CHILDREN (Fiep Bulletin - online, 2013)
Motor development is the process of change in motor behavior and is related to age, being dependent on the biology, behavior and environment. A good motor development may influence the child's future life in the social, intellectual and cultural, as to have some difficulty driving the child takes refuge in the middle which does not dominate consequently failing to perform or performing certain activities infrequently. Therefore, knowing the level at which the child is to such motor skills and coordination can be an important ally in physical education classes, considering that these data with the physical education teachers can direct their lessons according to the results. One way to know what level the child is is the use of tests such as KTK that aids in evaluating the child's motor development in particular for variable motor coordination, and test TGMD-2, in which both can directly influence motor development of the child. Investigations focused on analyzing the levels of coordination and motor skills of children, as well as the possible interaction between the two variables, are necessary in order to better orchestrate the physical education professional with performance assessment strategies. The aim of this study was to analyze the level of coordination and motor skills of children. The study included 15 children with an average age of 8 years (7.6), students of a private school in the city of Santos, who performed two types of tests to assess the level of gross motor skills and gross motor skills through TGMD-2 and KTK respectively. The results indicate a need, the group evaluated, be subjected to strategies that enhance the fundamental skills, considering these are compelling for purchases of more complex skills.
Keywords: Motor tests; Children; Motor Development